2022
DOI: 10.1111/bjd.21055
|View full text |Cite
|
Sign up to set email alerts
|

The associated burden of mental health conditions in alopecia areata: a population‐based study in UK primary care*

Abstract: Sequirus and Takedaall through his universities and none related to this study. W.S.C. is an employee of Pfizer Ltd. S.H. is principal investigator and C.T. is principal and (national) chief investigator on the Pfizer-funded ALLEGRO clinical trial in alopecia areata. M.H., A.E.M., S.H. and A.G.M. are members of the British Association of Dermatologists guidelines group for alopecia areata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 28 publications
(59 reference statements)
4
48
0
Order By: Relevance
“…Eight papers studied the prevalence of anxiety disorders in adults with AA ( n = 86,014). These studies reported point prevalence rates of 3.24% ( 64 ), 4% ( 17 ), 8.4% ( 71 ), and 13.70% ( 58 ). Several papers also reported that people with AA have a higher chance of being diagnosed with an anxiety disorder in comparison to healthy controls ( 13 , 15 , 17 , 64 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight papers studied the prevalence of anxiety disorders in adults with AA ( n = 86,014). These studies reported point prevalence rates of 3.24% ( 64 ), 4% ( 17 ), 8.4% ( 71 ), and 13.70% ( 58 ). Several papers also reported that people with AA have a higher chance of being diagnosed with an anxiety disorder in comparison to healthy controls ( 13 , 15 , 17 , 64 ).…”
Section: Resultsmentioning
confidence: 99%
“…These studies reported point prevalence rates of 3.24% ( 64 ), 4% ( 17 ), 8.4% ( 71 ), and 13.70% ( 58 ). Several papers also reported that people with AA have a higher chance of being diagnosed with an anxiety disorder in comparison to healthy controls ( 13 , 15 , 17 , 64 ). Prevalence rates of specific anxiety disorders in people with AA range from 7.4% for specific phobias and 22.2–39% for generalized anxiety disorders ( 57 , 66 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of the BJD , Macbeth and her seven coauthors provide a timely article regarding mental health conditions associated with alopecia areata (AA) 1 . In the past, this area has been neglected by many dermatologists and others when considering the treatment of AA, a problem we discussed nearly 20 years ago 2 .…”
mentioning
confidence: 99%